Concluding remarks: Cooperative phenomena in framework materials. (18th January 2021) - Jiang, Jianwen
Abstract : A brief summary and personal perspectives on the virtual Faraday Discussion : Cooperative Phenomena in Framework Materials (13–16 October 2020). Abstract : The Faraday Discussion on Cooperative Phenomena in Framework Materials took place online on 13–16 October 2020. At this unique meeting, there were impressive presentations and stimulating discussions on the current state and future direction of cooperative phenomena in framework materials, particularly flexible metal–organic frameworks or porous coordination polymers. This article aims to highlight the presentations and achievements at the meeting, and also discuss personal perspectives on the fundamental challenges for future exploration in this vibrant field.